Pengukuran Awal Konsentrasi Pb Di Kawasan Sungai Jawi Kota Pontianak - Winardi (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2015)
Pb concentration in the air mostly come from motor vehicle exhaust. There is a correlation between the levels of activity of motor vehicles with Pb concentration in the air. Research which is a combination of field and laboratory research is seeing Pb concentrations in the air at Jalan H. Rais A. Rahman, Sei Jawi Dalam Pontianak which is one of the areas with the densest vehicle activity in Pontianak, in different variations and then compared with the standard quality. This study consists of three variations, namely variations days (Monday till Sunday); variations in time (morning, afternoon, evening); height variation (1 m, 1.5 m, 2 m) were determined on the day and the maximum time to see the horizontal dispersion concentration of Pb in the air. With comparative and tabulation method and sought the maximum Pb concentration in time, the day and altitude. Based on the research results, obtained maximum Pb concentration in the morning and the minimum in the afternoon, except on Friday and Saturday, where the concentration of Pb afternoon more than the concentration in the afternoon. At the time of maximum Pb concentration morning on Monday and the minimum on Sunday. Tests were carried out on Monday morning, said that a Pb concentrated at a height of Â± 1.5 meters from the ground is 4.130 ppm.